Study of association of serum vitamin D and serum calcium with spontaneous aneurysmal subarachnoid haemorrhage in a tertiary care centre - Kuldeep Singh; Sharad Pandey; Pankaj Kumar; L.N. Gupta; Amit Mehto; Ravi Prakesh Jha (Romanian Neurosurgery, 2022)
Background: Aneurysmal subarachnoid haemorrhage (aSAH) is a disease associated with high mortality and morbidity. Recent studies have postulated a correlation between Vitamin D deficiency and aSAH, however, the mechanism of which remains obscure. Vitamin D and Calcium in patients withaSAH has not been formally investigated. Therefore, the aim of this study was to evaluate the incidence of hypovitaminosis D and hypocalcemia in patients with aSAH.